Timing the initiation of sex: Delay mechanisms alter fitness outcomes in a rotifer population model - Bethany L.F. Stevens; Silke F. van Daalen; Tirzah J. Blomquist; Kristin E. Gribble; Michael G. Neubert (Journal of Theoretical Biology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Short- and long-term impact of aseptic bathing strategies on the skin microbiome in ICU patients - Tilman E. Klassert; Cristina Zubiria-Barrera; Luisa A. Denkel; Mercedes Lopez; Robert Neubert; Amelya Keles Slevogt; Frank Bloos; P. Christian Schulze; Jörg Epstude; Petra Gastmeier; Christine Geffers; Hortense Slevogt (Medical Microbiology and Immunology, 2025)
Bathing strategies with antiseptic agents, such as Chlorhexidine and Octenidine, have been widely adopted to mitigate infection risks in intensive care units (ICU). However, concerns exist regarding their long-term effects on skin microbiome structures and potential unintended consequences, including antibiotic cross-resistance. This longitudinal study characterized the compositional changes of the skin microbiome of ICU patients upon these two antiseptic bathing strategies when compared to standard water and soap bathing. Samples were collected in a three-armed cluster randomized decolonization trial (registration number DRKS00010475). Skin swabs from 5 different sites and three time points were analyzed by culture-based methods, 16S rRNA-gene amplicon sequencing and multiplex Taq-Man assays for detection of antimicrobial resistance genes (ARG). Our results show that Chlorhexidine bathing led to a sustained reduction of the bacterial biomass on different skin sites, as measured by both molecular and culture-based methods. Thereby, the microbial structures remained largely unaltered both in their diversity and their taxonomic composition. However, the loss of microbiome site-specificity observed on the skin of ICU patients remained unchanged independently from the bathing strategy applied and persisted even after discharge. None of the antiseptic bathing strategies led to an increase or accumulation of antibiotic-resistance determinants on any of the skin sites investigated in this study. Thus, this study suggests that daily patient bathing with 2% Chlorhexidine impregnated cloths or 0.08% Octenidine wash mitts does not impact skin microbiome structures and antibiotic resistance gene accumulation in ICU patients when compared to non-antiseptic water and soap bathing routine.

Small Phytoplankton Community Composition Cycles Annually With a Coastal Bloom - Bethany L. F. Stevens; Rebecca J. Gast; Emily E. Peacock; Yogesh A. Girdhar; Michael G. Neubert; Heidi M. Sosik (Environmental Microbiology, 2025)
Small photosynthetic eukaryotes are a productive and dynamic component of marine planktonic communities. Here, we investigate how seasonal changes in the abundance of these primary producers relate to changes in their community composition at a coastal site on the Northeast US Shelf. We present a 9‐year time series of 18S rRNA sequencing data and identify gradual transitions within the pico‐ and nanoplankton community that occur repeatedly over the annual cycle. We compare these compositional changes to concurrent high‐resolution in situ flow cytometry measurements of eukaryotic phytoplankton abundance and division rate. We find that the Chlorophyta contribute a large proportion of the sequences in our samples and drive much of the seasonal variability within the small phytoplankton community. Across the time series, Bathycoccus , Micromonas and Picochlorum are the dominant genera, with the first being present year‐round, while Micromonas bravo and Picochlorum are representative of the summer community. We also find a strong winter Phaeocystis signal which might be leading to flow cytometry measurements of relatively large cells in the early spring. Our results provide fundamental knowledge of the taxonomic composition of the phytoplankton community on the Northeast US Shelf, improving our understanding of the region's diversity and compositional variability over time.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

Distinct responses to warming within picoplankton communities across an environmental gradient - Bethany L. F. Stevens; Emily E. Peacock; E. Taylor Crockford; Alexi Shalapyonok; Michael G. Neubert; Heidi M. Sosik (Global Change Biology, 2024)
Picophytoplankton are a ubiquitous component of marine plankton communities and are expected to be favored by global increases in seawater temperature and stratification associated with climate change. Eukaryotic and prokaryotic picophytoplankton have distinct ecology, and global models predict that the two groups will respond differently to future climate scenarios. At a nearshore observatory on the Northeast US Shelf, however, decades of year‐round monitoring have shown these two groups to be highly synchronized in their responses to environmental variability. To reconcile the differences between regional and global predictions for picophytoplankton dynamics, we here investigate the picophytoplankton community across the continental shelf gradient from the nearshore observatory to the continental slope. We analyze flow cytometry data from 22 research cruises, comparing the response of picoeukaryote and Synechococcus communities to environmental variability across time and space. We find that the mechanisms controlling picophytoplankton abundance differ across taxa, season, and distance from shore. Like the prokaryote, Synechococcus , picoeukaryote division rates are limited nearshore by low temperatures in winter and spring, and higher temperatures offshore lead to an earlier spring bloom. Unlike Synechococcus , picoeukaryote concentration in summer decreases dramatically in offshore surface waters and exhibits deeper subsurface maxima. The offshore picoeukaryote community appears to be nutrient limited in the summer and subject to much greater loss rates than Synechococcus . This work both produces and demonstrates the necessity of taxon‐ and site‐specific knowledge for accurately predicting the responses of picophytoplankton to ongoing environmental change.

Molecular investigation and description of Iberozospeum n. gen., including the description of one new species (Eupulmonata, Ellobioidea, Carychiidae) - Jeannette Kneubühler; Adrienne Jochum; Carlos E. Prieto; Eike Neubert (Organisms Diversity & Evolution, 2022)
The subterranean realm of the Cantabrian-Pyrenean region of northern Spain harbours a rich diversity of Zospeum . Due to their tiny size and the difficulty of finding them alive, scarce animal material has been available for scientific investigation. Recent investigations of Zospeum shells have provided valuable, but limited insights towards our understanding of the evolutionary processes occurring within this taxon in northern Spain. In an integrative study, we investigate 57 populations of Zospeum from northern Spanish caves using two mitochondrial (COI and 16S) and two nuclear markers (H3 and 5.8 S rRNA + ITS2). Revealed is a separate radiation of the northern Spanish species for which the new genus, Iberozospeum, is proposed. The independent radiation of Dinaric Zospeum from that of northern Spain justifies the designation of Iberozospeum n. gen. Morphological evidence is provided via histological analysis of Iberozospeum vasconicum and SEM analyses of radulae of eastern Alpine, Dinaric and Iberian species. Important differences in morphological structure and character states are presented, including the first view of the sexually mature female and the presence of the giant albumen gland in an individual of the subterranean, troglobitic Carychiidae. Significant differences are revealed in superficial crystallographic structure of the columellar lamellae, the morphology of the columellar muscle and in the radula. Radular ribbon length, ribbon broadness, straightness of the ribbon base and cusp configuration are distinctive in the Iberian species. One new species is described corroborated by genetic and morphological characters.

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Barium isotope fractionation during the experimental transformation of aragonite to witherite and of gypsum to barite, and the effect of ion (de)solvation - Michael E. Böttcher; Nadja Neubert; Katja von Allmen; Elias Samankassou; Thomas F. Nägler (Isotopes in Environmental and Health Studies, 2018)

Exploring the Ecology of Deep-Sea Hydrothermal Vents in a Metacommunity Framework - Lauren S. Mullineaux; Anna Metaxas; Stace E. Beaulieu; Monika Bright; Sabine Gollner; Benjamin M. Grupe; Santiago Herrera; Julie B. Kellner; Lisa A. Levin; Satoshi Mitarai; Michael G. Neubert; Andreas M. Thurnherr; et al. (Frontiers in Marine Science, 2018)

Barium isotope fractionation during experimental formation of the double carbonate BaMn[CO 3 ] 2 at ambient temperature - Michael E. Böttcher; Patrizia Geprägs; Nadja Neubert; Katja von Allmen; Chloé Pretet; Elias Samankassou; Thomas F. Nägler (Isotopes in Environmental and Health Studies, 2012)

Radiocarbon based assessment of soil organic matter contribution to soil respiration in a pine stand of the Campine region, Belgium - Tommaso Chiti; Rolf E. M. Neubert; Ivan A. Janssens; Jorge Curiel Yuste; Carmina Sirignano; Giacomo Certini (Plant and Soil, 2011)

Effects of branching spatial structure and life history on the asymptotic growth rate of a population - Emma E. Goldberg; Heather J. Lynch; Michael G. Neubert; William F. Fagan (Theoretical Ecology, 2010)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria - Thomas Müller; H.-J. Bätza; A. Beckert; C. Bunzenthal; J. H. Cox; C. M. Freuling; A. R. Fooks; J. Frost; L. Geue; A. Hoeflechner; D. Marston; A. Neubert; et al. (Archives of Virology, 2009)

Women encounter ADRs more often than do men - Y. Zopf; C. Rabe; A. Neubert; K. G. Gaßmann; W. Rascher; E. G. Hahn; K. Brune; H. Dormann (European Journal of Clinical Pharmacology, 2008)

Recent Results from Studies of Electric Discharges in the Mesosphere - T. Neubert; M. Rycroft; T. Farges; E. Blanc; O. Chanrion; E. Arnone; A. Odzimek; N. Arnold; C.-F. Enell; E. Turunen; T. Bösinger; Á. Mika; et al. (Surveys in Geophysics, 2008)

What can we learn about the lipid vesicle structure from the small-angle neutron scattering experiment? - M. A. Kiselev; E. V. Zemlyanaya; V. K. Aswal; R. H. H. Neubert (European Biophysics Journal, 2006)

On the Estimation of Dispersal Kernels from Individual Mark-Recapture Data - Masami Fujiwara; Kurt E. Anderson; Michael G. Neubert; Hal Caswell (Environmental and Ecological Statistics, 2006)

Body size and food web structure: testing the equiprobability assumption of the cascade model - M. G. Neubert; S. C. Blumenshine; D. E. Duplisea; T. Jonsson; B. Rashleigh (Oecologia, 2000)

Mixing Ratios and Photostationary State of NO and NO2 Observed During the POPCORN Field Campaign at a Rural Site in Germany - F. Rohrer; D. Brüning; E. S. Grobler; M. Weber; D. H. Ehhalt; R. Neubert; W. Schüßler; I. Levin (Journal of Atmospheric Chemistry, 1998)

Four generation reproductive toxicity study with 2,3,7,8-tetrachlorodibenzo-P-dioxin (TCDD) in rats - E. Koch; E. Thiel; E. Chahoud; D. Neubert (Archives of Toxicology, 1995)

Influence of 13-cis and all- trans retinoic acid on rat embryonic development in vitro: correlation with isomerisation and drug transfer to the embryo - S. Klug; J. Creech Kraft; E. Wildi; H. -J. Merker; T. V. N. Persaud; H. Nau; D. Neubert (Archives of Toxicology, 1989)

LD50 versus acute toxicity - R. Baß; P. Günzel; D. Henschler; J. König; D. Lorke; D. Neubert; E. Schütz; D. Schuppan; G. Zbinden (Archives of Toxicology, 1982)